Survey Analysis for Indigenous Policy in Australia: Social Sciences Perspectives (CAEPR Monograph 32) - Hunter, Boyd (CAEPR Monograph, 2012)
Indigenous policy is a complex domain motivated by a range of social, cultural, political and economic issues. The Council of Australian Governments 'closing